Diseño y construcción de un sistema de medida de temperatura para la criopreservación de homoinjertos cardiovasculares - TemperMed - Bustamante O., John; Gallón L., Alejandra; Cuartas R., Diego (Revista Mexicana de Ingenieria Biomedica, 2002)
The Temperature Measurement System for the Cryopreservation of Cardiovascular Homografts (TemperMed) is an "automatized system for the register, storage and later data manipulation of the temperature of biological tissue in a cooling process, and its objective is to optimize and to guarantee a technique that allows conserving the quality of tissue processed, with a decrease of costs in the process. The developed system allows us to register the temperature of two homografts simultaneously; it does not require the personnel permanence during the time demanded by the process; it introduces guarantees of precision in the temporary intervals between one and the other measurement, and in the same data; it ties optimal instrumental elements in relation to the particular characteristics of the process; and in general, it facilitates the analysis and the comparison of results that are going to be related to the variables and curves of cooling, as well as the refining of the process. For the development of the TemperMed project an instrumental phase was implemented in which a physical prototype was constructed, simultaneously an application was developed in Visual-Basic®, presenting a friendly interface that satisfies the necessities raised in the process of cryopreservation; finally, tests were made that allowed us to validate the functionality of the system.